2021
DOI: 10.3390/polym13101650
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Methods in Studies of Liquid Crystal Elastomers

Abstract: Liquid crystal elastomers (LCEs) are a type of material with specific features of polymers and of liquid crystals. They exhibit interesting behaviors, i.e., they are able to change their physical properties when met with external stimuli, including heat, light, electric, and magnetic fields. This behavior makes LCEs a suitable candidate for a variety of applications, including, but not limited to, artificial muscles, optical devices, microscopy and imaging systems, biosensor devices, and optimization of solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 136 publications
(314 reference statements)
0
12
0
Order By: Relevance
“…However, theoretical and computer models, which quantitively describe the relation between stimulus and/or material parameters and the induced deformations, are being developed to facilitate the development of programable LCN devices. The recent overview of the results in this research direction can be found in (Soltani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, theoretical and computer models, which quantitively describe the relation between stimulus and/or material parameters and the induced deformations, are being developed to facilitate the development of programable LCN devices. The recent overview of the results in this research direction can be found in (Soltani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the present investigation consists primarily in discussing multiscale modeling techniques, and only a limited number of works are addressed when they concern each individual physical phenomenon. Interested readers are kindly referred to a more comprehensive review of numerical methods of liquid crystal polymers [48].…”
Section: Multiscale Analysis Of Nematic Solidsmentioning
confidence: 99%
“…Furthermore, multiscale methods where one or two numerical methods are intertwined have also been proposed [21][22][23]. Interested readers are referred to recent reviews [24,25] on numerical methods and multiscale methods, respectively. This review primarily aims to disseminate continuum-based models regarding the phase behavior of responsive materials.…”
Section: Introductionmentioning
confidence: 99%